2017
DOI: 10.1016/j.canlet.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Modified-FOLFIRINOX in metastatic pancreatic cancer: A prospective study in Chinese population

Abstract: FOLFIRINOX chemotherapy has shown remarkable responses in patients with metastatic pancreatic cancer (MPC), and has significantly improved prognosis. However, FOLFIRINOX is currently not frequently applied in China because of its high incidence of adverse events, and there is no recognized optimization for this therapy in Chinese population. Modification of FOLFIRINOX may be better for its acceptance in China. In this study, we evaluated the efficacy and safety of modified-FOLFIRINOX in patients with MPC. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 17 publications
2
53
2
Order By: Relevance
“…Nevertheless, there were no detected pathogenic variants in genes regulating DNA damage response like BRCA1, BRCA2, ATM, and PALB2. It is worthwhile for further investigation as a significant proportion of patients develop acquired drug tolerance (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there were no detected pathogenic variants in genes regulating DNA damage response like BRCA1, BRCA2, ATM, and PALB2. It is worthwhile for further investigation as a significant proportion of patients develop acquired drug tolerance (14).…”
Section: Discussionmentioning
confidence: 99%
“…All included patients received FOLFIRINOX therapy as firstline treatment except one undergoing initial surgery. This regimen was modified by reducing Oxaliplatin and Irinotecan to 85% and 75% of their full dose, respectively, and omitting the Fluorouracil intravenous bolus (14). Assessment of treatment response was performed every four cycles of chemotherapy via abdominal enhanced CT and enhanced MRI of the liver.…”
Section: Study Patientsmentioning
confidence: 99%
“…5 Trials with modified FOLFIRINOX (mFOLFIRINOX) have been conducted in which 5-FU, irinotecan, and/or oxaliplatin have been dose-reduced to decrease toxicity. [8][9][10][11] A phase 2 trial showed improved safety and maintained efficacy of mFOLFIRINOX in metastatic pancreatic cancer compared with historical controls. 8…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer remains the fourth leading cause of cancerrelated death over the world in 2015 [1], with a 5-year survival rate of 1-5% [2]. In 2015, there are approximately 90,100 new pancreatic cancer patients in China, with an estimated 79,400 deaths [3,4]. Of all cancers, pancreatic cancer is ranked 10th in incidence and mortality is ranked 7th [3].…”
Section: Introductionmentioning
confidence: 99%